Damming a Crane Habitat: Habitat Conservation of Black-Necked Cranes Wintering in Zemithang Valley, Arunachal Pradesh, India - Bhattacharya, Malyasri; Watham, Taibangba; G.V., Gopi (Journal of the Bombay Natural History Society (JBNHS), 2024)
One of the very few wintering habitats of the Near Threatened Black-necked Crane in India faces extreme threats due to an upcoming hydroelectric project in Nyamjang-chu river Valley in Arunachal Pradesh. A study was carried out from June 2017 to March 2018 in Zemithang, Tawang district to understand the habitat suitability of the Black-necked Crane and local perception about the conservation of the species. Riverine islands and riparian vegetation form the critical ground for the species. The direct impact on habitat will be the submergence of the total upstream study area by 63%, inundating more than 91% of the Hippophae area and 85% of the seasonal sandbars, leaving only 15% of the prime foraging ground of the Black-necked Crane. Moreover, questionnaire surveys revealed majority of the people were against the construction of the dam. Results also indicated that indirect impacts from the construction of dam and pollution would collapse the other suitable habitats located nearby. These findings will help in the conservation planning of the fragile wintering habitats of the Black-necked Crane.